Distinguishing pediatric and adolescent renal cell carcinoma from other renal malignancies. Issue 5 (2nd November 2016) - Syed, Jamil S.; Nguyen, Kevin A.; Wu, Charlotte Q.; Cost, Nicholas G.; Siddiqui, Mohummad M.; Hittelman, Adam B.; Shuch, Brian
Abstract: Purpose: Renal cell carcinoma (RCC) represents a small proportion of renal malignancies early in life. Distinguishing RCC from other malignancies is important as treatment strategies may differ. We analyze the Surveillance Epidemiology, and End Results (SEER) database to identify predictive factors of RCC in the pediatric population with renal tumors. Methods: We queried SEER to identify patients from ages 0 to 19 diagnosed with a renal malignancy between 1973 and 2013. Cases were sorted using histology and site codes. Age‐adjusted standardized incidence rates (SIR) were calculated. We compared differences in characteristics between cancer types. A logistic regression model and a nomogram were created to identify predictors of RCC. Results: A total of 3, 670 patients were identified, of which 281 (7.7%) were diagnosed with RCC. The SIR of RCC increased with age. After age 12, RCC was found in >50% of all newly diagnosed cases. On multivariate analysis, RCC was associated with smaller tumor size ( P < 0.001), increasing age ( P < 0.001), black race ( P < 0.001), and localized stage ( P < 0.001). The nomogram predicted RCC pathology with a concordance index of 0.965. Conclusions: RCC in childhood and adolescence is relatively uncommon; however, it accounts for >50% of renal malignancies after age 12. For every year of increasing age, the odds of having an RCC diagnosis are increased by 50%. The odds of a renal tumor being RCC are increased in black children, those with localized disease, and those with smaller tumors. In these specific populations, RCC should be favored in the differential diagnosis of the renal mass.